NOTES ON MEXICAN DRUGS PLANTS AND FOODS XI DISTRIBUTION OF THE AMINOACIDS IN PROTEINS OF CERTAIN INSECT EGGS AHAUAUTLE - DESCHAMPS, IGNACIO; BACHSTEZ, MARCELO (Hospital General, CD MEXICO, DF, MEX, 1941)
Views on interpretation and use of terms by various authorities are treated This list was presented before the 13th International Congress of Zoology, in the Sect of Nomenclature, at the meeting in Paris, July 1948Here, 3 points were preposed; (1) separ
CIENC MEX
Keywords: NOTES, MEXICAN DRUGS, PLANTS, FOODS XI DISTRIBUTION, AMINOACIDS, PROTEINS, CERTAIN INSECT EGGS AHAUAUTLE; MULTIDISCIPLINARIA; TECNOLOGIA DE LOS ALIMENTOS; ELABORACION DE ALIMENTOS